Mucosal-Associated Invariant T Cells Develop an Innate-Like Transcriptomic Program in Anti-mycobacterial Responses - Sharma, Manju; Zhang, Shuangmin; Niu, Liang; Lewinsohn, David M.; Zhang, Xiang; Huang, Shouxiong (Frontiers in Immunology, 2020)
Conventional T cells exhibit a delayed response to the initial priming of peptide antigens presented by major histocompatibility complex (MHC) proteins. Unlike conventional T cells, mucosal-associated invariant T (MAIT) cells quickly respond to non-peptidic metabolite antigens presented by MHC-related protein 1 (MR1). To elucidate the MR1-dependent activation program of MAIT cells in response to mycobacterial infections, we determined the surface markers, transcriptomic profiles, and effector responses of activated human MAIT cells. Results revealed that mycobacterial-incubated antigen-presenting cells stimulated abundant human CD8+ MAIT cells to upregulate the co-expression of CD69 and CD26, as a combinatorial activation marker. Further transcriptomic analyses demonstrated that CD69+CD26++ CD8+MAIT cells highly expressed numerous genes for mediating anti-mycobacterial immune responses, including pro-inflammatory cytokines, cytolytic molecules, NK cell receptors, and transcription factors, in contrast to inactivated counterparts CD69+/-CD26+/- CD8+MAIT cells. Gene co-expression, enrichment, and pathway analyses yielded high statistical significance to strongly support that activated CD8+ MAIT cells shared gene expression and numerous pathways with NK and CD8+ T cells in activation, cytokine production, cytokine signaling, and effector functions. Flow cytometry detected that activated CD8+MAIT cells produced TNF, IFN, and granulysin to inhibit mycobacterial growth and fight mycobacterial infection. Together, results strongly support that the combinatorial activation marker CD69+CD26++ labels the activated CD8+MAIT cells that develop an innate-like activation program in anti-mycobacterial immune responses. We speculate that the rapid production of anti-mycobacterial effector molecules facilitates MAIT cells to fight early mycobacterial infection in humans.